2020
DOI: 10.1002/jcp.29560
|View full text |Cite
|
Sign up to set email alerts
|

YY1‐PVT1 affects trophoblast invasion and adhesion by regulating mTOR pathway‐mediated autophagy

Abstract: Insufficient trophoblast invasion is the key factor for the occurrence of recurrent spontaneous abortions (RSA). Our previous studies identified Yin Yang 1 (YY1) as a transcription factor involved in the regulation of trophoblast invasiveness at the maternal-fetal interface. Long noncoding RNAs (lncRNAs) can regulate gene expression and autophagy in many ways. The purpose of this study was to explore the relationship between YY1 and lncRNAs and the mechanism by which lncRNAs affect the biological behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…6G–I ). In agreement with the previous studies showing that YY1 is implicated in autophagy in multiple cells 47 , 48 , we then confirmed that YY1 positively regulated the LC3B protein expression in the newborn ovaries (Supplementary Fig. S5A ).…”
Section: Resultssupporting
confidence: 92%
“…6G–I ). In agreement with the previous studies showing that YY1 is implicated in autophagy in multiple cells 47 , 48 , we then confirmed that YY1 positively regulated the LC3B protein expression in the newborn ovaries (Supplementary Fig. S5A ).…”
Section: Resultssupporting
confidence: 92%
“…Recurrent spontaneous abortion (RSA) is a common complication of human pregnancy defined by two or more abortions before the 20th gestational week. The incidence of RSA is approximately 1–5%, with an increasing tendency in recent years [ 138 ]. RSA occurrence is associated with trophoblast insufficiency and impaired remodeling of the spiral arteries into low-resistance blood vessels.…”
Section: Lncrnas and Other Pregnancy-related Disordersmentioning
confidence: 99%
“…RSA occurrence is associated with trophoblast insufficiency and impaired remodeling of the spiral arteries into low-resistance blood vessels. Yang et al has recently reported that the expression of the lncRNA-PVT1 is significantly reduced in tissues from RSA patients [ 138 ]. They also demonstrated that knockdown of lncRNA-PVT1 significantly reduced adhesion, invasion, autophagy, and mTOR expression in HTR-8/SVneo cells, which significantly increased apoptosis.…”
Section: Lncrnas and Other Pregnancy-related Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yin Yang 1, a transcription factor for the cytoskeleton-related proteins whose mRNA level was shown to be lower in recurrent spontaneous abortion patients, has been identified as a regulator of autophagy in trophoblasts [52,53]. In addition, Fetuin-A, an endogenous inhibitor of the insulin receptor, which increases in women with gestational diabetes mellitus, inhibits autophagy via repression of beclin1 (BECN1) [54].…”
Section: Autophagy In Preeclampsiamentioning
confidence: 99%